2008
DOI: 10.3177/jnsv.54.196
|View full text |Cite
|
Sign up to set email alerts
|

Myo-Inositol Treatment Increases Serum Plasmalogens and Decreases Small Dense LDL, Particularly in Hyperlipidemic Subjects with Metabolic Syndrome

Abstract: Summary Background and aim: We have previously shown that serum plasmalogen levels positively correlate with HDL, and significantly decrease with aging, and may be related to LDL particle size. The objective of the present study was to investigate the effects of increased serum plasmalogens on lipidosis, particularly the appearance of atherogenic small dense LDL (sdLDL), of subjects with hyperlipidemia and metabolic syndrome (MetS). Methods and results: The effects of increased serum plasmalogen levels, induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…Similarly to C22:0, C24:0 and C24:1, serum levels of PlsCho and the resultant PlsCho/PlsEtn and PlsCho/PL ratios of MetS subjects were significantly reduced compared to non-MetS subjects Table 3 . This result is in agreement with our previous study, in which hyperlipidemic subjects with MetS showed a considerable reduction in serum levels of both classes of plasmalogens compared to those without MetS 37 . In addition, these VLCFAs as well as C20:4 in serum lipids showed a significant positive correlation, particularly with PlsCho-related parameters Table 5 .…”
Section: Discussionsupporting
confidence: 83%
“…Similarly to C22:0, C24:0 and C24:1, serum levels of PlsCho and the resultant PlsCho/PlsEtn and PlsCho/PL ratios of MetS subjects were significantly reduced compared to non-MetS subjects Table 3 . This result is in agreement with our previous study, in which hyperlipidemic subjects with MetS showed a considerable reduction in serum levels of both classes of plasmalogens compared to those without MetS 37 . In addition, these VLCFAs as well as C20:4 in serum lipids showed a significant positive correlation, particularly with PlsCho-related parameters Table 5 .…”
Section: Discussionsupporting
confidence: 83%
“…These diseases are often substantially deficient in Pls, because part of Pls' biosynthetic enzymes are localized in this organelle. 2 Recently, serum (or plasma) Pls have gained interest in several clinical symptoms such as metabolic syndrome/atherosclerosis 3,4 or Alzheimer's disease 5 other than peroxisomal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Monounsaturated long-chain fatty acids such as oleic acid (C18:1) and erucic acid (C22:1), myo-inositol, and Pl precursors, alkylglycerol and HG, have been reported to increase Pl levels in laboratory animals and humans [19][20][21][22][23]. However, they unexpectedly reduced the gene expression of Pl biosynthetic enzymes in HepG2 cells (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, we attempted to increase the levels of plasma Pls as a preventative strategy for diseases associated with oxidative stress and aging. This was achieved in laboratory animals as well as humans through administration of the Pl precursor alkylglycerol [19], myoinositol (MI) [20,21], monounsaturated long-chain fatty acids [22], and the hypolipidemic agent, statin [23]. However, their effects on the gene expression of Pl biosynthetic enzymes remain unknown.…”
Section: Introductionmentioning
confidence: 99%